Efektivitas Sari Belimbing Wuluh terhadap Daya Ikat Air dan Susut Masak Daging Paha Itik Magelang - Fitria Mayasari; Nur Hidayah; M. Haris Septian (Wahana Peternakan, 2022)
Duck is a type of poultry that can be consumed as a new option other than chicken meat. Several types of local ducks can be utilized their potential for community consumption, one of which is Magelang duck. Duck meat is one of the foodstuffs of livestock origin that contains nutrients that are good for the human body. The weakness of meat with a high nutritional content that can cause meat susceptible to contamination by decaying microorganisms. Efforts to maintain meat quality are to prevent microbial contamination of Magelang duck meat by using bilimbi fruit liquid (Averrhoa bilimbi L.) to maintain the quality of duck meat. This study aims to determine the efficiency using bilimbi fruit liquid with different concentrations on the value of water holding capacity and cooking loss of Magelang duck thigh meat. The experiment plan used in this study was a Completely Randomized Experimental Design (CRD) with 4 treatments differences concentration of using bilimbi fruit liquid (0, 20, 40, 60%) and 5 replays with immersion for 30 minutes. The data obtained was analyzed with a variety analysis (ANOVA) and the apparent differences between treatments were analyzed with the Duncan Multiple Range Test (DMRT) advanced test. The results showed that soaking magelang duck thigh meat up to a concentration of 60% of using bilimbi fruit liquid for 30 minutes did not give a noticeable influence or has not been able to increase DIA and decrease cooking. The range of DIA values in this study is 40.67˗44.93% and cooked stacking 47.19–52.37%. Keywords: magelang duck, water holding capacity, starfruit juice, cooking loss.